The clinical validity of atlantoaxial joint inclination angle and reduction index for atlantoaxial dislocation - Qu, Yang; Du, Yukun; Zhao, Yonghua; Li, Jianyi; Luo, Hao; Zhou, Jiaxiang; Xi, Yongming (Frontiers in Surgery, 2023)
Objective Atlantoaxial dislocation patients with neurological defects require surgery. Sometimes, release surgery is necessary for irreducible atlantoaxial dislocation to further achieve reduction. Whether release surgery is essential relies on the surgeon's experience and lacks objective reference criteria. To evaluate the value of atlantoaxial joint inclination angle (AAJI) in sagittal and coronal planes and reduction index (RI) in the surgical approach selection for atlantoaxial dislocation. Methods Retrospectively analyzed 87 cases (42 males and 45 females, 9–89 years) of atlantoaxial dislocation from January 2011 to November 2020. In addition, 40 individuals without atlantoaxial dislocation were selected as the control group. Imaging parameters were compared between the two groups. According to surgical methods, the experiment group was divided into two groups including Group A(release surgery group) and Group B (conventional operation group). The parameters were measured based on CT and x-ray. The relevant imaging parameters and clinical scores, including the AAJI in sagittal and coronal planes, the atlas-dens interval (ADI) before and after traction, the RI, and JOA scores were measured and analyzed. Results The sagittal and coronal atlantoaxial joint inclination angles(SAAJI and CAAJI) in the control group were 7.91 ± 0.42(L), 7.99 ± 0.39°(R), 12.92 ± 0.41°(L), 12.97 ± 0.37°(R), in A were 28.94 ± 1.46°(L), 28.57 ± 1.55°(R), 27.41 ± 1.29°(L), 27.84 ± 1.55°(R), and in B were 16.16 ± 0.95°(L), 16.80 ± 1.00°(R), 24.60 ± 0.84°(L), 24.92 ± 0.93°(R) respectively. Statistical analysis showed that there was a statistical difference in the SAAJI between the control group and the experiment group (P < 0.01), as well as between groups A and B (P < 0.01). The RI in groups A and B was 27.78 ± 1.46% and 48.60 ± 1.22% respectively, and there was also a significant difference between the two groups (P < 0.01). There was negative correlation between SAAJI and RI. Conclusions The SAAJI and RI can be used as objective imaging indexes to evaluate the reducibility of atlantoaxial dislocation. And these parameters could further guide the selection of surgery methods. When the RI is smaller than 48.60% and SAAJI is bigger than 28.94°, anterior release may be required.